The portrayal of mental health in Australian daily newspapers - Stephanie Kenez; Paul O'Halloran; Pranee Liamputtong (Australian and New Zealand Journal of Public Health, 2015)
Abstract Objective: To examine how mental health is portrayed as a holistic construct in three major Australian daily newspapers. Methods: Using an unobtrusive, mixed methods approach incorporating content and thematic analyses, data were collected from hard copies of The Age, The Australian and Herald Sun newspapers and their weekend counterparts over 12 weeks in 2012. Results: Newspaper coverage of mental health favoured stories about illness over wellbeing. While the issue was typically reported responsibly, psychotic disorders were overrepresented in discussions of illness and were often discussed in relation to deviance. Conclusions: Our analysis suggested that positive mental health messages are commonly presented, particularly in tabloid coverage, which appears to place greater emphasis on wellbeing. However, improvements in the representation of psychotic disorders appear to be less progressive than other disorders. This suggests mental health professionals and organisations need to continue building relationships with and providing education to journalists to ensure responsible representations continue to dominate. Implications: This study provides an updated and holistic examination of the media's portrayal of mental health within the Australian context. As this is the first study to examine the portrayal of wellbeing and illness, it may provide insight into how media representations of mental health affect society beyond those affected by illness.